Sexual conflict in its ecological setting. (27th August 2018) - Perry, Jennifer C.; Rowe, Locke
Abstract : Sexual conflict can lead to rapid and continuous coevolution between females and males, without any inputs from varying ecology. Yet both the degree of conflict and selection on antagonistic traits are known to be sensitive to local ecological conditions. This leads to the longstanding question: to what extent does variation in ecological context drive sexually antagonistic coevolution? In water striders, there is much information about the impacts of ecological factors on conflict, and about patterns of antagonistic coevolution. However, the connection between the two is poorly understood. Here, we first review the multiple ways in which ecological context might affect the coevolutionary trajectory of the sexes. We then review ecological and coevolutionary patterns in water striders, and connections between them, in light of theory and new data. Our analysis suggests that ecological variation does impact observed patterns of antagonistic coevolution, but highlights significant uncertainty due to the multiple pathways by which ecological factors can influence conflict and its evolutionary outcome. To the extent that water striders are a reasonable reflection of other systems, this observation serves as both an opportunity and a warning: there is much to learn, but gaining insight may be a daunting process in many systems. This article is part of the theme issue 'Linking local adaptation with the evolution of sex differences'.